Introduction of managed entry agreements in Korea: Problem, policy, and politics - Kim, Hyungmin; Godman, Brian; Kwon, Hye-Young; Hong, Song Hee (Frontiers in Pharmacology, 2023)
Objectives: This study aimed to understand Managed Entry Agreements (MEAs) in Korea through the framework of three streams of the policy window model and its practical management and impact on pricing and reimbursement scheme. Methods: An extensive literature review based on Kingdon’s model was conducted. We also performed descriptive analyses of MEA implementation using data on medicines listed in Korea and compared its MEA scheme with four different countries. Results: As per problem streams, patients with rare disease or cancers have considerable difficulties in affording theire medicines and this has challenged the drug benefit system and raised an issue of patient’s access. Policy streams highlighted that MEAs were introduced as a benefit enhancement plan for four major diseases since January 2014. MEAs have also been strengthened as a bypass mechanism to expand the insurance coverage especially for new premium-priced medicines under Moon Care (Listing all non-listed services). In descriptive analysis of MEAs, a total of 48 medicines were contracted as MEAs from January 2014 to December 2020, accounting for 73.4% of listed medicines for cancer or rare diseases and 97.9% of the cases were finance-based contracts. Meanwhile, outcome-based contracts such as CED accounted for only 2.1%. The application of MEAs differs across countries, resulting in a kappa coefficient of 0.00-0.14(UK 0.03, Italy 0.00, Australia 0.14), indicating a lack of consistency compared to South Korea. Conclusion: MEAs, which were introduced as a bypass mechanism, have now superseded the standard process for anticancer agents or orphan drugs. Further studies are needed to evaluate the impact of the confidential agreements and effectiveness of new high-priced medicines with limited clinical data at launch.